Pemberdayaan Siswa SMP Sebagai Kader SIMANTIK (Siswa Pemantau Jentik) Dalam Upaya Pencegahan Endemi Malaria Di Kabupaten Keerom - Frans A. Asmuruf; Inriyanti Assa; Yohanis I Mandik; Sherly A.W. Ramandey; Lamria Simanjuntak; Sriyanto (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Malaria is a significant public health issue in Keerom Regency, Papua. This community service aimed to improve the knowledge and skills of junior high school students through the SIMANTIK (Siswa Pemantau Jentik) education and training program. The activity was conducted at three schools: SMPN 2 Arso 3, SMP YPPK Taruna Tegasa, and SMPN 7 Yetti, involving 143 students. The methods included pre-test, material presentation on malaria vectors and life cycles, practical larva monitoring, and post-test evaluations. The paired sample t-test showed a significant increase in students' knowledge before and after the training (p < 0.05), with an average score increase ranging from 10% to 40% across the three schools. However, regression analysis indicated varying impacts of knowledge and attitude on student behavior regarding malaria prevention. In conclusion, SIMANTIK training effectively increases knowledge, necessitating sustained monitoring clubs in schools to maintain malaria-free environments.